UPAYA PENCEGAHAN PEROKOK PEMULA MELALUI PROGRAM SIAGA (SATU IKATAN AKSI GERAKAN ANTI ROKOK) DI SMPN 23 PADANG - Wira Iqbal; Erle Mabel; Jihan Muqsithoh Masand; Rahma Aulya; Syafa’ati Dzikra Prijan; Rezi Fatrima Surya (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Today's adolescents face serious challenges related to smoking behavior. This is a crucial issue that requires immediate action through effective educational methods. An interactive educational approach that actively involves adolescents is considered more successful in addressing this issue. This community service activity aims to increase motivation to quit smoking and prevent students of SMPN 23 Padang from starting to smoke for the first time. The aim is to enhance students' understanding of the dangers of smoking through an engaging educational approach. The program will be implemented from October to December 2024, adopting interactive methods such as counseling, emotionally arousing demonstrations, group discussions, experiments, and educational games. The active involvement of students, teachers, and school student organizations (OSIS) will ensure the creation of a school environment that supports a healthy lifestyle. The success of this program is expected to be seen from the high enthusiasm of students and the active participation of teachers. To ensure sustainability, Anti-Smoking Ambassadors will be established, who will continue the prevention and education efforts after the main program ends. The results of this initiative show that a participatory education approach is a practical strategic solution in reducing smoking prevalence among adolescents. It is also an essential step in creating a smoking-free younger generation. It is hoped that this program can be continued sustainably. In addition, it is hoped that this activity can be developed and implemented in the broader area to provide a greater positive impact in preventing smoking among adolescents.